Structural Analysis and Five-Layered Control Frame Work for Underground Pipe Inspection Robot - Satheesh Kumar Gopal; Ajin M (Institute of Advanced Engineering and Science, 2016)
Design of a robot generally involves various types of analyses that invariably include structural, numerical, kinematic, dynamic and experimental analysis. A robot designed as a solution for social problems would have to undergo all these stages before it is incorporated in-situ. The authors in continuation to their earlier work [1] are presenting the results of structural analysis in this paper. Initially a detailed description of the anatomy of the proposed robot is provided for clarity along with the identified design parameters. The primary design parameter ‘load to power ratio’ establishes certain geometric and structural constrains on the design of links comprising the robot. This relationship is studied in order to improve to the load to power ratio of the robot. A significant reduction in weight is achieved by working on these variables which leads to the improvement in the functional aspects too, viz., reduced torque requirement from the motor. Upon finalizing on the choice of motors and sensors the 5 layered control architecture based on statespace representation is also presented. Fuzzy logic based control algorithm is proposed to unite the layered approach depending on the task allocated to the robot.